Structural adjustments and agriculture / by Ashok Gulati and Shashanka Bhide - Gulati, Ashok; Bhide, Shashanka (New Delhi, 1993)
Economic Reforms have been ushered in in the Indian economy since July 91 Macro economic reforms in the form of trade and exchange rate policies and controlling the fiscal deficits are affecting all the sectors. The structural reforms in industry are directly affecting the industrial sector, but also having implications for other sectors. What is likely to be the impact of these Macro and Micro Reforms on Indian Agriculture is the subject matter that Dr. Ashok Gulati and Dr. Shashanka Bhide have tried to explore in this paper They have pointed out the linkages between trade reforms, industrial reforms and their implications for agriculture. They also focus specifically on the Urea segment of Fertiliser Industry. They attempt to delineate broadly the implications of decontrol in the Urea sector (under alternative scenarios). Another interesting point that they take up for analysis is the impact of reforms on private investment in agriculture and thereby on the growth momentum of this important sector of the economy.
Keywords: Agriculture Economic aspects 1991